RISK ANALYSIS OF THE LIFE INSURANCE PROGRAM FOR BINA MANDIRI UNIVERSITY STUDENTS GORONTALO - Rahayu agustina Ishak (LP2M Universitas Bina Mandiri Gorontalo, 2025)
Insurance has several benefits, including first, minimizing unexpected risks, second, the family will be more secure, third, many things can be prepared. Such as children’s education, monthly family expenses, fourth, various kinds of facilities can be obtained through life insurance, fifth, reassurance thoughts in the future. The method used in this research is descriptive qualitative, with the analysis technique of this research, namely reducing data, by means collect and summarize the main things obtained from the results of deep interviews with respondents, then processing them into data sources. The population in this study are students at the Bina Mandiri Gorontalo. With several assessments result sub-themes, namely insurance services welfare, social health security, management risk and financial literacy.